Interrelation of tumor infiltrating lymphocyte subpopulations with clinical and pathomorphological features of a breast cancer - O. A. Beznos; D. A. Burov; V. Yu. Sel'chuk; I. K. Vorotnikov; V. V. Timoshenko; T. A. Grigor'eva; Ya. V. Vishnevskaya; N. N. Tupitsyn (ABV-press, 2016)
Levels of intratumoral lymphocytes have direct interrelations with clinical, morphological and biological characteristics of tumor. Rates of CD4+lymphocytes rise in a process of increase of tumor size. At the same time, content of intratumoral CD4+CD25+ lymphocytes is maximal at small size tumors. In the absence of metastases of a breast cancer in the regional lymph nodes are noted a higher content of activated (HLA-DR+) intratumoral T-lymphocytes (CD3, CD4, CD8), which is represented in a higher levels of HLA-DR+CD45+ lymphocytes in patients with a lack of metastasis in comparison with patients, who has metastasis. In case of II and III grade of breast cancer malignancy the percent of intratumoral lymphocytes is higher, in comparison to I grade malignancy. The rate of intratumoral lymphocytes as well as activated T-cells (CD3) and T-helpers (CD4) is higher in stage I of breast cancer, then in II-III stages. The number of intratumoral CD3+ T-lymphocytes and CD8+ cells is higher in tumors with low level of Ki-67+ proliferated cells. Authentically higher content of activated T-cells and activated CD4+ lymphocytes is noted in HER-2 / neu-negative cases. Higher content of CD4+CD3+ T-lymphocytes was noted in 2-3 scores of HER-2 / neu than negative HER-2 / neu status. At an infiltrative ductal cancer authentically higher levels of infiltration of a tumor are revealed by the lymphocytes, activated T-cells and activated T-killers CD3+CD8+. Tumor infiltration levels in luminal A cancer are 5 times higher, then in luminal B (10,5 and 2,2 % correspondingly). At the same time, luminal B subtype is characterized by higher tumor infiltration of T-lymphocytes (81 and 70 %).